Human Capital Development and Poverty Reduction in Nigeria: Investigating the Nexus - Abasilim, Ugochukwu D.; Oparah, Adeline C. Onyekwuo- (Universitas Medan Area, 2025)
This study investigates the relationship between human capital development and poverty reduction through education, health care, and the acquisition of skills and investment within the Nigerian context. This study aims to determine if human capital development fosters poverty reduction through education and health care investments and if gaps exist in existing policies developed by the government concerning human capital development. This qualitative research uses secondary data sources, including books, journal articles, government documents, and reputable online databases. Data were analysed and identified for patterns of relationship through thematic analysis. The findings show a strong positive relationship between human capital development and poverty reduction. However, the study indicates that insufficient investment in critical components of human capital, such as education and healthcare, partly accounts for the enduring prevalence of poverty. Lastly, the government and non-governmental organisations must carefully coordinate their policy initiatives for resource distribution and human capital development for effective, long-lasting poverty reduction.